An unusual cause of hiccups. Issue 5 (September 1996) - Perry, S; Stevenson, J
Abstract : A case of persistent hiccup associated with cavitating pulmonary tuberculosis is reported. Though tuberculosis presenting with hiccup is rare, tuberculosis is again on the increase and clinicians should remain alert to the possibility of this diagnosis.